Integrating Mbojo Folklore and Culture Preneurship to Shape Modern Leadership Values - Alaini, Nining Nur; Hidayatullah, Dede; Saefuddin, Saefuddin; Supriadi, Asep; Rohim, Rohim; Ali, Tengku Intan Marlina Tengku Mohd (Aptisi Transactions On Technopreneurship (ATT), 2025)
The Mbojo community in West Nusa Tenggara has a folklore entitled "Oi Wobo". Like fairy tales or myths that always contain messages, this "Oi Wobo" folklore reflects the values of the Mbojo community. This Oi Wobo story becomes important when we look back at why the Mbojo people feel the need to pass down and teach these values through folklore, and see whether the old concepts of ancestral heritage contained in the Oi Wobo story today can be contextualized or relevant to the challenges that exist today. Through semiotic studies and literary sociology conducted, it is known that Oi Wobo folklore, one of them, reveals values related to the concept of leader and leadership of the Mbojo community. The concept of leader and leadership of the Mbojo community reflected in the folklore "Oi Wobo" adheres to the concept of nggusu waru. From the studies that have been conducted, it can also be concluded that the concept of leadership of the Mbojo community, which is based on the philosophy of nggusu waru, can be recontextualized or relevant to today's leadership challenges. The ignorance and incomprehension of the Mbojo people towards these values causes that thenoble values related to leaders and leadership are not widely realized in today's leadership. Thus, this study is important so that the values of the noble ancestral heritage can be known, understood and reused to achieve a more quality community life.